An Efficiency Case for Cost Equalisation in a Regional Economy with Migration Externalities - Petchey, Jeffrey (School of Economics and Finance, CBS, 2015)
Cost equalisation, which redistributes income from low to high cost sub-national regions,is practised in many unitary and federal countries as part of broader schemes designed toequalise scal capacities. While these policies are motivated by equity, in this paper I showthat under plausible circumstances cost equalisation enhances economic eciency. Therationale for this striking result has to do with the way that cost dierences across regionsinteract with externalities caused by migration and the role of inter-regional transfers as acorrective instrument. By providing an eciency rationale for cost equalisation, the paperbuilds a more eective bridge between the theory and practice of scal equalisation.